The Soul of a New Machine: Bioethicists in the Bureaucracy - Elliott, Carl (Cambridge quarterly of healthcare ethics, 2005)
In a recent issue of The Lancet, the historian Roger Cooter predicted that the field of bioethics will soon die of self-inflicted wounds. “Conspiring against it,” he wrote, “is exposure of the funding of some of its US centres by pharmaceutical companies; exclusion of alternative perspectives from the social sciences; retention of narrow analytical notions of ethics in the face of popular expression and academic respect for the place of emotions; divisions within the discipline (including one over its origins and meaning); and collusion with, and appropriation by, clinical medicine.” Cooter's prognosis? “Hardly wet behind the ears, bioethics seems destined for a short lifespan.”